RSC: Gel dosimetry as a tool for clinical implementation of image-guided radiotherapy. Issue 1 (1st January 2022) - Elter, A; Dorsch, S; Marot, M; Gillmann, C; Johnen, W; Runz, A; Spindeldreier, C K; Klüter, S; Karger, C P; Mann, P
Abstract: The implementation of new image-guided radiotherapy (IGRT) treatment techniques requires the development of new quality assurance (QA) methods including geometric and dosimetric validation of the applied dose in 3D. Polymer gels (PG) provide a promising tool to perform such tests. However, to be used in a large variety of clinical applications, the PG must be flexibly applicable. In this work, we present a variety of phantoms used in clinical routine to perform both hardware and workflow tests in IGRT. This includes the validation of isocenter accuracy in magnetic resonance (MR)-guided RT (MRgRT) and end-to-end tests of online adaptive treatment techniques for inter- and intra-fraction motion management in IGRT. The phantoms are equipped with one or more PG containers of different materials including 3D printed containers to allow for 3D dosimetry in arbitrarily shaped structures. The proposed measurement techniques and phantoms provide a flexible application and show a clear benefit of PG for 3D dosimetry in combination with end-to-end tests in many clinical QA applications.